O006/#1066 Randomized trial of pelvic radiation with and without concurrent cisplatin in patients with a pelvic only recurrence of endometrial cancer. (4th December 2022) - Klopp, Ann; Enserro, Danielle; Powell, Matthew; Randall, Marcus; Feddock, Jonathan; Schink, Julian; Bender, David; Kushnir, Kristina; Backes, Floor; Zweizig, Susan; Waggoner, Steven; Bradley, Kristin; et al.
Abstract : Objectives: The pelvis is a common site of recurrence for patients with endometrial cancers. A randomized trial was conducted to compare progression-free survival in patients treated with radiation therapy alone as compared to radiation therapy with concurrent cisplatin-based chemotherapy. Methods: 165 Patients were accrued between February 2009 and August 2020. Women with recurrent endometrial carcinoma limited to the pelvis were eligible. The median time for follow up for vital status was 60 months. Results: Most patients had grade 1 or 2 endometroid endometrial cancer (81%) and most recurrences were vaginal (86%). Radiation therapy was delivered to the pelvis with 3D or IMRT techniques followed by HDR or LDR interstitial or intracavitary brachytherapy. Chemotherapy was delivered with weekly cisplatin. Grade 4 or higher acute adverse event were reported in 8 participants in the chemotherapy and radiation arm as compared to 1 treated with radiation only. 68% of patients treated with radiation therapy were alive and progression-free as compared to 59.8% of those that received chemotherapy and radiation. Overall, patients treated with weekly cisplatin had a lower rate of PFS as compared to patients treated with radiation alone (stratified HR=1.40, 95% CI: 0.82–2.39, p=0.8919). Conclusions: Results of this randomized trial suggest that the addition of chemotherapy does not improve, and may worsen, outcomes for patients treated with definitive radiation therapy for recurrent endometrial cancer. Those with low grade and vaginal apex recurrences may be best treated with radiation therapy alone.